GAYA KEPEMIMPINAN WALIKOTA DAN WAKIL WALIKOTA MAKASSAR - Muhammad Ilham Ekaputra; Djabir Hamzah; Sumardi Sumardi (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Leadership is needed because it has the responsibility to move, direct, influence and lead the people they lead to jointly realize the goals of the organization. This study aims to analyze the influence of autocratic leadership style, democratic, free control, participatory, visionary and transformational to the performance of employees at the Government of Makassar City Period 2014 - 2019; and analyze among the dominant leadership style influence on employee performance at Makassar City Government Period 2014 - 2019. This research is a survey with quantitative research. The population of the research is 11.449 employees of Makassar City Government and the research sample is determined using Slovin formula 5% obtained by 387 respondents as respondents. Data collection techniques used questionnaires and documentation techniques. Data analysis used is Multiple Linear Regression. The results showed that the leadership style of autocracy gave a negative effect on the performance of employees of Makassar City Government Office. Furthermore, leadership style in the form of democratic style, free control, participative, visionary and transformational have positive and significant influence to the performance of employees at Makassar City Government Office period 2014 - 2019. Also found variables dominant leadership style (X5) which is based on regression coefficient value nilai . This means that the achievement of the work of each employee in realizing the achievement of organizational goals is determined more by the leadership style of the leadership that can give leadership significance to each subordinate either as a direction selter, agent of change, spokenperson or as a coach that affect the achievement of employee performance in quantity , quality, efficient utilization of time and effectiveness of budget usage. Keywords: Leadership Style, Autocratic, Democratic, Free Control, Participatory, Visionary, Transformational and Performance